THE ROLE AND TASKS OF THE INTERNAL AUDIT AND AUDIT COMMITTEE AS BODIES SUPPORTING EFFECTIVE CORPORATE GOVERNANCE IN INSURANCE SECTOR INSTITUTIONS IN POLAND - Szczepankiewicz, Elżbieta Izabela (Oeconomia Copernicana, 2012)
Faced with the risk of consecutive waves of financial crisis and economic recession, government committees, financial supervision authorities and financial institutions themselves – both in Poland and worldwide – have launched a number of measures to make the supervision of insurance sector institutions more effective, particularly in aspects related to efficient risk management and internal control. The article describes the impact of the amendment of laws and other regulations on the development of the present internal control systems in insurance sector institutions. It draws attention to the need for a new structure of the internal control system, and the role and purpose of the internal audit and the audit committee as the bodies supporting effective supervision in insurance undertakings and reinsurance undertakings.